İmmigration politics in Germany civil society and problems of immigrants - Tanverdi- Dernac, İpek (My University, 2005)
Göç olgusuyla uzun yıllardır karşı karşıya olmasına rağmen Almanya’nın bir göç ülkesi olmanın sorumluluklarını ve sonuçlarını anlaması uzun bir bekleyişi gerektirmiştir. Alman vatandaşlarının kafasında Alman olmanın değişik karşılıkları vardır. Bu çeşitlilik siyasal partilerin göç konusuna yaklaşımında kendini göstermiştir. Göç karşıtı tutumuyla tanınmalarına rağmen Almanya’nın göçe olan ihtiyacı siyasal partilerin gözardı edemeyeceği bir gerçek haline gelmiştir. Azalmakta olan nufüs ve doğum oranları Almanya için göçü gerekli kılmıştır. Almanya’ya özgü vatandaşlık anlayışı ve buna bağlı olarak, yabancılara karşı tutum değişik dönemlerde farklılık göstermiş ve bu farklılıklar yabancılara karşı şiddet içeren aktiviteler ve ırk ayrımının artışıyla ortaya çıkmıştır. Berlin Duvarı’nın yıkımı ile Almaya’nın kitleler halinde göçmen akımıyla karşılaşmaşı bu ülkenin çeşitli bölgelerinde yabancı karşıtı radikal davranışların artmasına yol açmıştır. New York’taki Dünya Ticaret Merkezine yapılan 11 Eylül saldırıları ve dünyanın diğer kesimlerinde meydana gelen terrörist saldırılar Müslüman nufüsa olan tepkileri arttırmıştır. Bütün bu gelişmeler Almanya ve Göç konusunun güncelliğini ve ilginçliğini korumuş, ayrıca uyum konusunun Almanya gibi göçmen gerçeğiyle başbaşa yaşamak zorunda olan bir ülke için ne kadar önemli olduğunu göstermiştir. Siyasi partilerin tam desteği ve sivil toplum kuruluşlarının katkıları olmadan sürdürülebilir bir uyum ve huzur ortamı yaratılması mümkün değildir.

Immigration has been a popular theme for researchers, immigration and Germany as well. The issue keeps its actuality and attractiveness especially coupled with the issue of integration. Germany has a long immigration history as it has been a passageway for immigrants for centuries with its geographical location. The post war immigration history of the country is shaped pretty much by the recruitment of foreign workers to compensate the lacking work force. Under the coverage of this framework millions of people settled permanently in Germany. Today Germany has a multi ethnic society and has to face the challenges of that. Accordingly immigration has always been one of the most sensitive issues in German political agenda and one of the most influential tools of the election campaigns which can be observed in varying approaches of the political parties to the issue. Considering its economic problems, population developments and huge number of foreign population, it is time for Germany to pay greater attention to the problems of immigrants. The prospects show that Germany will stay as an attractive destination for immigration. No matter how will be the future picture of immigration in Germany, immigration is today an unavoidable reality of the country. The politicians and the society should work hand in hand to create the desired model of multicultural society. The civil society organizations and the distribution of offers of those organizations in different regions play an important role in that process especially to facilitate the interaction between the natives and the immigrants to create a healthy society which could live in harmony.
Keywords: Avrupa Birliği; Göç_Almanya